Tinjauan Hukum Terhadap Kompetensi Peradilan Tata Usaha Negara dalam Menyelesaikan Sengketa Tanah - Bunga, Marten (Gorontalo Law Review, 2018)
The scope of land disputes that became the competence of the State Administrative Judicature according to the judicial principle adopted in Indonesia, the implementation of the Decision of the State Administrative Court in the settlement of land disputes.This research is conducted through normative legal approach (juridical normative), that is how law is utilized as an instrument to realize the application of land dispute resolution mechanism through authority to try State Administration Court. This research uses normative legal research type to identify and analyze legal factor which is an obstacle in the application of legislation, where this study refers to the laws and regulations on land and State Administration Judicature Law, court decisions and other legal materials.That the State Administration Dispute in the field of land arises because of a written stipulation issued by the State Administration or Administrative Officer containing State Administration law action which in accordance with the prevailing laws and regulations has been concrete, individual and final in the form of land certificate of ownership the right to land issued by the Government. Implementation of the Decision of State Administration which has been decided and has the force of law in practice raises a polemic in the community where the State Administration officials are not willing to carry out the decision of the Administrative Court of the State. This condition is caused because the State Administrative Court is not the executor (executor of the decision) but only as supervisor of the implementation of the decision, for all government actions in order not to violate the law and the role of legal protection for the community.